At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

solve using substitution
-5x+7y=-5
y=-5
x=?


Sagot :

So if you solve for x using the first equation, you get: x = 5y - 5.

From there you can plug that into the second equation which would give you:

7y-5y+5=-23

Simplifying from that point, you get y = -9.

Now that you have one of the values, you can solve for x by plugging it back into the equation we made (x = 5y - 5) and getting to the answer x = -40.

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.